Maize monoculture causes niacin deficiency in free-living European brown hares and impairs local population development - Selimovic, Aldin; Tissier, Mathilde L.; Arnold, Walter (Frontiers in Ecology and Evolution, 2022)
Maize (Zea mays) is the most produced crop worldwide and the second most important bio-energy plant. Huge maize monoculture is considered a threat to biodiversity in agricultural landscapes and may also contribute to the decline of European brown hares (Lepus europaeus, Pallas 1778). Indeed, the intensification of agriculture has been identified as one of the main factors responsible for the decline of brown hare populations. A reason why large maize cultures can be particularly detrimental to animals consuming this plant is its poor nutritional value with respect to niacin. In this study, we investigated the effects of the proportion of area under maize crops on liver concentrations of niacin in free-living hares, on the reproductive output of does (females), and on the development of local populations, at nine study sites in Lower Austria. Hare numbers were estimated from spotlight counts in spring and autumn. Liver samples and uteri were obtained from hares shot in the same areas during regular autumn hunts. Number of offspring born to an individual female during the preceding reproductive period was determined by counting placental scars. Our results show a significant negative effect of the area under maize crops on liver concentrations of niacin of does and on their reproductive output. Further, we found a significant negative effect of the area under maize on the development of a population. Altogether, our findings indicate that high proportions of the area under maize crops contribute to the decline of brown hares by reduced fecundity of does and impaired development of local populations.